The second leg home advantage: Evidence from European football cup competitions - Page, L.; Page, K. (Journal of Sports Sciences, 2007)
The home advantage is a widely acknowledged sporting phenomenon, especially in association football. Here, we examine the second leg home advantage, an effect that is discussed in the public domain but which has received very little scientific attention. The second leg home advantage effect occurs when on average teams are more likely to win a two-stage knock-out competition when they play at home in the second leg. That is, both teams have a home advantage but this advantage is significantly greater for the team that plays at home second. Examining data from three different European Cup football competitions spanning 51 years, we show that the second leg home advantage is a real phenomenon. The second leg home team has more than a 50% probability to qualify for the next round in the competition even after controlling for extra time and team ability as possible alternative explanations. The second leg home advantage appears, however, to have decreased significantly over the past decade. Possible reasons for its existence and subsequent decline are presented.